2022
DOI: 10.1101/2022.06.16.496520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A unitary model of auditory frequency change perception

Abstract: Changes in the frequency content of sounds over time are arguably the most basic form of information about the behavior of sound-emitting objects. In perceptual studies, such changes have mostly been investigated separately, as aspects of either pitch or timbre. Here, we propose a unitary account of “up” and “down” subjective judgments of frequency change, based on a model combining auditory correlates of acoustic cues in a sound-specific and listener-specific manner. To do so, we introduce a generalized versi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…We found that discrimination was only partially invariant to real-world differences in spectral envelope between different vowels or instruments. Judgments were biased depending on whether the spectral envelope shifted congruently or incongruently with the f0, consistent with previous studies (Allen & Oxenham, 2014; Chuang & Wang, 1978; Hellström et al, 1994; Kuhl & Miller, 1982; Micheyl & Oxenham, 2004; Miller, 1978; Moore & Glasberg, 1990; Repp & Lin, 1990; Siedenburg et al, 2022; Singh & Hirsh, 1992; Stoll, 1984). However, invariance was similarly limited for harmonic and inharmonic tones, indicating that invariance does not depend on representations of f0 (addressing the first question).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that discrimination was only partially invariant to real-world differences in spectral envelope between different vowels or instruments. Judgments were biased depending on whether the spectral envelope shifted congruently or incongruently with the f0, consistent with previous studies (Allen & Oxenham, 2014; Chuang & Wang, 1978; Hellström et al, 1994; Kuhl & Miller, 1982; Micheyl & Oxenham, 2004; Miller, 1978; Moore & Glasberg, 1990; Repp & Lin, 1990; Siedenburg et al, 2022; Singh & Hirsh, 1992; Stoll, 1984). However, invariance was similarly limited for harmonic and inharmonic tones, indicating that invariance does not depend on representations of f0 (addressing the first question).…”
Section: Introductionsupporting
confidence: 89%
“…We built on previous studies examining pitch discrimination between tones differing in spectral envelope (Allen & Oxenham, 2014; Chuang & Wang, 1978; Hellström et al, 1994; Kuhl & Miller, 1982; Micheyl & Oxenham, 2004; Miller, 1978; Moore et al, 1992; Moore & Glasberg, 1990; Repp & Lin, 1990; Russo & Thompson, 2005; Siedenburg et al, 2022; Singh & Hirsh, 1992; Stoll, 1984; Warrier & Zatorre, 2002), by using comparisons between harmonic and inharmonic stimuli to test whether invariances in pitch perception are dependent on f0-based pitch. In both Experiment 1 (speech) and Experiment 2 (musical instruments), participants showed above-chance up-down discrimination irrespective of whether the instruments or speakers being compared were the same or different.…”
Section: Discussionmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 1, 2022. ; https://doi.org/10. 1101/2022 to in-channel cancellation. In the harmonic cancellation model, all peripheral channels are filtered by a cancellation filter with the same delay parameter 𝑇 , whereas here 𝑇 is set independently in each channel.…”
Section: In-channel Vs Harmonic Cancellationmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 1, 2022. ; https://doi.org/10. 1101/2022 The in-channel cancellation model can be invoked to support an array of in-channel frequency shift detectors, for example as schematized in Fig. 14.…”
Section: Pitch Pitch Change Transparency Tonalitymentioning
confidence: 99%
See 1 more Smart Citation